1982
DOI: 10.3382/ps.0612166
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Flock Uniformity on the Reproductive Performance of Broiler Breeder Hens Housed in Cages and Floor Pens

Abstract: Two flocks of broiler breeder hens, differing in uniformity of body weight, were evaluated under cage and floor management systems over a 28-week period. Hens were housed singly in cages (N = 280) or in litter floor pens (N = 304). Caged hens were artificially inseminated with .05 ml of pooled semen once weekly. Floor birds were mated naturally. During the first 10 weeks of production, the more uniform flock exhibited significantly higher egg production than the less uniform flock. Uniformity did not influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…In order to minimize this problem, which can adversely affect flock performance (Petitte et al, 1982), most breeder flocks are fed using the skip-a-day (SAD) method. However, as this method does not consistently improve flock uniformity, another method of feed restriction, namely skip-twodays (STD), was proposed by Zeitlin and Soller (1982).…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize this problem, which can adversely affect flock performance (Petitte et al, 1982), most breeder flocks are fed using the skip-a-day (SAD) method. However, as this method does not consistently improve flock uniformity, another method of feed restriction, namely skip-twodays (STD), was proposed by Zeitlin and Soller (1982).…”
Section: Introductionmentioning
confidence: 99%
“…In a study to test uniformity of body weight in broiler breeders maintained on the litter floor versus cages, Petitte et al (1982) observed no significant differences in productive performance among flocks of 80% and 89% of body weight uniformity. They also observed that caged broiler breeders produced significantly more eggs than floor maintained breeders during peak egg production, but cumulative egg production was not significantly different.…”
Section: Cage Versus Litter Floor Managementmentioning
confidence: 96%
“…Broiler breeders housed in cages lay heavier eggs than their litter floor managed counterparts (Petitte et al, 1982). In three trials Petitte et al (1983) evaluated production efficiency of cage maintained broiler chicks versus floor maintained broiler breeders.…”
Section: Cage Versus Litter Floor Managementmentioning
confidence: 99%
“…According to Petitte et al (1982) broiler breeders maintained in cages produce heavier eggs than those managed on litter floors. Petitte et al (1983) compared production efficiency of broiler breeders artificially inseminated in cages to those naturally mated in floor pens.…”
Section: Egg Productionmentioning
confidence: 99%
“…According to Petitte et al (1982) broiler breeders housed in cages produce heavier eggs than those managed on litter floors. Also (Petitte et al, 1983), a comparision of production efficiency of broiler breeders artificially inseminated in cages to those naturally mated in floor pens demonstrated no difference embryonic death, although hatchability was significantly lower in the eggs collected in the cages.…”
Section: Cage Versus Litter Floor Managementmentioning
confidence: 99%